Genetic variants in Apolipoprotein AV alter triglyceride concentrations in pregnancy - Ward, Kirsten J (BioMed Central, 2003)
BACKGROUND: Triglyceride concentrations are raised in pregnancy and are considered a key fetal fuel. Several gene variants are known to alter triglyceride concentrations, including those in the Apolipoprotein E (ApoE), Lipoprotein Lipase (LPL), and most recently, the Apolipoprotein AV (ApoAV) gene. However, less is known about how variants in these genes alter triglyceride concentrations in pregnancy or affect fetal growth. We aimed to determine the effect of the recently identified ApoAV gene on triglycerides in pregnancy and fetal growth. We assessed the role of two ApoAV haplotypes, defined by the C and W alleles of the -1131T>C and S19W polymorphisms, in 483 pregnant women and their offspring from the Exeter Family Study of Childhood Health. RESULTS: The -1131T>C and S19W variants have rare allele frequencies of 6.7% and 4.9% and are present in 13.4% and 9.7% of subjects respectively. In carriers of the -1131C and 19W alleles triglyceride concentrations were raised by 11.0% (1.98 mmol/ l(1.92 – 2.04) to 2.20 mmol/l (2.01 – 2.42), p = 0.035; and 16.2% (1.97 mmol/l (1.91 – 2.03) to 2.29 mmol/l (2.12 – 2.48), p < 0.001 respectively. There is nominally significant evidence that the -1131T>C variant is having an effect on maternal height (164.9 cm (164.3 – 165.5) to 167.0 cm (165.2 – 168.8), p = 0.029). There was no evidence that ApoAV genotype alters any other anthropometric measurements or biochemistries such as High Density Lipoprotein Cholesterol (HDL-C) or Low Density Lipoprotein Cholesterol (LDL-C). There is nominally significant evidence that the presence of a maternal -1131C variant alters fetal birth length (50.2 cm (50.0 – 50.4) to 50.9 cm (50.3 – 51.4), p = 0.022), and fetal birth crown-rump length (34.0 cm (33.8 – 34.1) to 34.5 cm (34.1 – 35.0), p = 0.023). There is no evidence that ApoAV genotype alters fetal birth weight or other fetal growth measurements. CONCLUSION: In conclusion variation in the ApoAV gene raises triglyceride concentrations in pregnancy, as well as normolipaemic states and there is preliminary evidence that it alters fetal growth parameters.